Effectiveness analysis of deceleration capacity and traditional heart rate variability in diagnosing vasovagal syncope - Guo, Yongzhe; Lin, Tao; Lin, Nanyu; Lin, Huizhong (Frontiers in Cardiovascular Medicine, 2024)
Background Vasovagal syncope (VVS) is a prevalent medical condition with a lack of efficient methods for its detection. Aim This study aimed to explore an objective clinical indicator in diagnosing VVS. Methods The retrospective analysis involved clinical data of 243 syncope patients from 1 June 2020 to 31 July 2023. Among them, 108 patients had a negative result in the tilt test (TTT), while the remaining 135 patients had a positive result in the TTT. Relevant statistical methods were utilized to examine the correlation between VVS and different indicators of heart rate variability. Results After screening, 354 patients being considered for VVS were evaluated, resulting in a final sample size of 243. Sex, age, deceleration capacity (DC), and standard deviation of all normal-to-normal intervals (SDNNs) were the variables that showed statistical significance between the TTT(−) group and the TTT(+) group. Independent risk factors identified by multivariate logistic regression were DC [odds ratio (OR) 1.710, 95% confidence interval (CI) 1.388–2.106, P < 0.001] and SDNN (OR 1.033, 95% CI 1.018–1.049, P < 0.001). Comparing the groups, receiver operating characteristic analysis revealed a notable distinction in both DC and SDNN [the respective areas under the curve were 0.789 (95% CI 0.730–0.848) and 0.702 (95% CI 0.637–0.767); the cutoff values were 7.15 and 131.42; P < 0.001, respectively]. Conclusion In summary, DC can function as an impartial and easily accessible clinical marker for differentiating VVS. A value exceeding 7.15 ms might suggest a higher likelihood of syncope.